УЛЫЎМА БИЛИМЛЕНДИРИЎ МЕКТЕП ЖАСЫНДАҒЫ БАЛАЛАРДА ТӘЛИМ -ТӘРБИЯ ЖУМЫСЛАРЫНЫҢ НӘТИЙЖЕЛИЛИГИН АСЫРЫЎДЫҢ ӘҲМИЙЕТИ - Нурланов, А.; Жумамуратов, Ш. (FAN va JAMIYAT, 2016)
The formation of personality in the society is the main task and responsibility of the educational work at school. The article deals with the issues of improving effectiveness of educational work in the formation of students’ personality at the general educational schools.